Cloning and characterization of zebrafish K2P13.1 (THIK-1) two-pore-domain K+ channels - Staudacher, Ingo; Seehausen, Sebastian; Gierten, Jakob; Illg, Claudius; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (Journal of molecular and cellular cardiology, 2019)
Two-pore-domain potassium (K2P) channels conduct background potassium currents in the heart and other tissues. K2P currents are involved in the repolarization of action potentials and stabilize the resting membrane potential. Human K2P13.1 (THIK-1) channels are expressed in the heart and have recently been implicated in atrial fibrillation. The in vivo significance of K2P13.1 currents in cardiac electrophysiology is not known. We hypothesized that Danio rerio (zebrafish) may serve as model to elucidate the functional role of cardiac K2P13.1 channels. This work was designed to characterize zebrafish orthologs of K2P13.1. Two zkcnk13 coding sequences were identified by DNA database searches and amplified from zebrafish cDNA. Human and zebrafish K2P13.1 proteins exhibit 70% (K2P13.1a) and 66% (K2P13.1b) identity. Kcnk13 expression in zebrafish was studied using polymerase chain reaction. Zebrafish kcnk13a and zkcnk13b mRNAs were detected in brain and heart. Human and zebrafish K2P13.1 currents were analyzed in the Xenopus oocyte expression system by voltage clamp electrophysiology. Zebrafish K2P13.1a polypeptides were non-functional, while zK2P13.1b channels exhibited K+ selective, outwardly rectifying currents. Zebrafish and human K2P13.1 currents were similarly activated by arachidonic acid and reduced by barium, mexiletine, lidocaine, and inhibition of phospholipase C. In conclusion, zebrafish K2P13.1b channels and their human orthologs exhibit structural and regulatory similarities. Zebrafish may be used as in vivo model for the assessment of physiology and therapeutic significance of K2P13.1.